A escrita da emigração : Memórias e estudos do arquivo familiar do galego Francisco Moura - Sarmiento, Erica (2015)
The article discusses the memories and the history stored in the family archive of Francis Mouro, migrant in Rio de Janeiro, in the first half of the twentieth century. The Mouro family, since the nineteenth century, decided to adopt Brazil as preferred destination. However, like so many Galician families also choose other destinations, moving to Portugal, Uruguay and Argentina. Through letters and personal documents preserved by the immigrant family is possible to reconstruct the migratory chains formed over more than half a century, the solidarity networks and migration of a city of intense immigration to Rio de Janeiro, as the galego city Santa Comba
O artigo aborda as memórias e a história guardadas no arquivo familiar de Francisco Mouro, emigrante no Rio de Janeiro, na primeira metade do século XX1. A família Mouro, desde o século XIX, resolveu adotar o Brasil como destino preferencial. Entretanto, como tantas famílias galegas, também abraçaram outros destinos, deslocando-se para Portugal, Uruguai e Argentina. Através das cartas e documentos pessoais preservados pelos familiares do imigrante é possível reconstruir as cadeias migratórias formadas ao longo de mais de meio século, as redes de solidariedade e os fluxos migratórios de um município de intensa imigraçao a Rio de Janeiro, como foi o concelho galego de Santa Comba
Keywords: Memories; Immigration; Personal files; Galician; Letters; Memórias^lpt; Imigraçao; Arquivos pessoais; Galego; Cartas